Cases Report On The Management Of Hospital Acquired Pneumonia In Ischemia Stroke Patients - Lasmaria Flora Roslinda Silaen (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Pneumonia is defined as acute inflammation of the pulmonary parenchyma caused by bacteria, viruses, fungi, parasites. Nosocomial pneumonia (Hospital Acquired Pneumonia) is pneumonia that is acquired while being hospitalized, at least after 48 hours of treatment and not in the incubation period. The average incidence of HAP is 5-15 per 1000 residents of hospital cases, while in the intensive care unit it is around 25%, where 70-80% of episodes of pneumomia occur when using a ventilator. Sentry Antimicrobial surveillance research found that 80% of nosocomial pneumonia bacteria are caused by six pathogenic bacteria, namely Staphilococcus aureus, Pseudomonas aeruginosa, Klebsiella species, E coli, Acinetobacter species and Enterobacter species. It was reported that a 68-year-old woman came to the emergency room four days before entering the hospital with a sudden decrease in consciousness while resting. Patients admitted with GCS 10 were treated in the room with a diagnosis of ischemic recurrent stroke + type 2 DM + Hypertension + Anemia. After eleven days of being treated in the room, the patient experienced shortness of breath, decreased saturation and GCS was decreasing, diagnosed with ischemic stroke + HAP + respiratory failure, intubated and connected to a ventilator in the ICU.